Voltage stress mitigation in high-gain DC-DC converters via dual Z-source DC-DC converter - Jawahar Marimuthu; Arockiaraj Sesaiya; Bhavani Ramachandran; Ramya Hyacinth Lourdusamy (Institute of Advanced Engineering and Science, 2026)
This paper presents a novel dual Z-source DC-DC converter designed to address the limitations of conventional high step-up converters used in renewable energy applications such as solar photovoltaic systems and fuel cells. Traditional boost and impedance-source converters often suffer from high voltage stress, low efficiency at higher power levels, and complex multi-stage configurations. To overcome these challenges, the proposed topology integrates a hybrid structure comprising symmetrical inductors and capacitors, enabling high voltage gain at reduced duty cycles while minimizing component stress. The converter is analytically modelled and evaluated under continuous conduction mode, and its performance is verified through MATLAB/Simulink simulations and experimental validation using a hardware prototype. The results demonstrate that the proposed converter achieves a voltage gain of up to 10× with a duty cycle below 0.5, while maintaining efficiency above 95% and significantly reducing voltage stress across switching devices. Compared to existing high step-up converters, the proposed design offers improved efficiency, reduced component count, and enhanced reliability. These features make it a promising solution for efficient and sustainable energy conversion in modern renewable energy systems.